Evidence Based Medicine: A Paradigm for Clinical Practice - Reddy, KR (Journal of Gandaki Medical College-Nepal, 2018)
Evidence based medicine (EBM) is the integration of best research evidence with clinical expertise and patient values. In the practice of EBM it is the physician’s duty to find the best and most current information and apply it judiciously for the benefit of the patient.The practice of EBM involves formulating a clear clinical question from a patient’s problem, searching the literature to acquire the evidence, then critically appraising the evidence for its validity and usefulness, and applying the results by implementing useful findings into clinical practice, and finally evaluating this application of evidence on patient. An important rule in EBM is that it starts with the patient and ends with the patient.Evidence based medicine requires new skills of the physician, including efficient literature searching and the application of formal rules of evidence evaluation from the clinical literature.Incorporation of EBM into one’s practice will not only make one a better clinician, it also allows one to provide the best possible quality of medical care to his or her patients. Thus EBM can be incorporated as an integral part of the medical curriculum.